Unsung Heroes Of The Operating Room: The Crucial Role Of Anesthesia Technicians (Journal of Namibian Studies : History Politics Culture, 2023)
Anesthesia technicians play a crucial yet often overlooked role in the operating room, supporting anesthesiologists and ensuring the safe delivery of anesthesia during surgical procedures. This abstract highlights the key responsibilities and contributions of anesthesia technicians, including preparation and setup, patient monitoring, assistance to anesthesiologists, emergency response, equipment maintenance, and team collaboration.